Removal of Anionic Direct Dye Using Zn/Al, Zn/Fe and Zn/Cr Layered Double Hydroxides Toward Interlayer Distance - Palapa, Neza Rahayu; Taher, Tarmizi; Mohadi, Risfidian; Lesbani, Aldes (Science and Technology Indonesia, 2019)
In order to minimize harmful effect of synthetic dye (direct yellow and direct violet) the capacity of Zn/Al, Zn/Cr and Zn/Fe layered double hydroxides of these contaminant was studied in this work. Batch adsorption experiment was conduct to investigate the effect of various operating parameters such as contact time, initial dye concentration and adsorption temperature in order to provide optimal condition in removal synthetic dye. Based on result, the sorption of direct dye onto LDHs followed pseudo-second-order rate model. The equilibrium adsorption data for both direct dye was fitted Freundlich isotherm model